Defying “conversion therapies” of LGBTQ+ persons in Africa: Queering Ruth and Boaz’s encounter at the threshing floor - Davids, Hanzline (Stellenbosch Theological Journal, 2024)
The contestation around Lesbian, Gay, Bisexual, Transgender, Queer and plus all other (LGBTQ+) persons’ genders and sexual identities is considered a colonial inheritance and modern Western imposition. Within this contested space, faith, politics, and culture play a fundamental role in inciting violence on the non-heteronormative embodiment of an LGBTQ+ person’s Sexual Orientation, Gender Identity, and Expression of Sex Characteristics (SOGIESC). One of the ways religion, culture, and politics collectively incite violence is through “conversion therapies”, which exacerbates LGBTQ+ vulnerabilities. This pseudo-therapy’s goal is to convert and suppress the SOGIESC of LGBTQ+ persons, thus leading to life-denying conditions. To counter “conversion therapies”, this article is interested in the encounter between Ruth and Boaz on the threshing floor as a site of situational vulnerability. The Hebrew Bible emphasises the depiction of threshing floors as sacred spaces. Threshing floors are traditionally used for essential life-sustaining activities such as food and sustenance. Therefore, this article seeks to queer the holy space of the threshing floor by using nego-feminism, queer agency and third space as theoretical frameworks. This article thus seeks to contribute to the knowledge production of queer agency in spaces of situational vulnerability.